The Effect of Passive Smoking on Total Antioxidant Capacity of Serum and Saliva in Rats - Motalebnejad, Mina; Pouramir, Mahdi; Moghadamnia, Ali-Akbar; Ghasemi, Leila; Soleimani, Laleh (Journal of Dental School, 2020)
Objective: Active and passive smoking lead to the production of a number of oxidants and antioxidants with various adverse health effects compromising the immune system. Tobacco use increases the production of free radicals as well. The purpose of this study was to determine the effects of passive smoking on total antioxidant capacity (TAC) of serum and saliva in rats. Methods: This experimental study was conducted on 18 rats with an age range of 7-11 weeks weighing 160-200 g; 9 of them were exposed to cigarette smoke 3 times daily for 8 minutes. The 9 controls were not exposed to cigarette smoke. After injection of 0.2 mg/kg midazolam and 0.5 mg/kg pilocarpine, serum and saliva samples were taken from subjects in the exposure and control groups at 0, 15 and 30 days. Serum cotinine was measured using ELISA kit. TAC of saliva and serum was measured using ferric reducing antioxidant power (FRAP) assay. TAC values at different time points were statistically analyzed in each group using Repeated Measures ANOVA and compared between the two groups using t-test. Results: At baseline, no significant difference existed between the two groups in terms of serum cotinine concentration but at days 15 and 30, cotinine serum concentration significantly increased in the exposure group. At baseline and 30 days, no significant difference existed between the two groups of passive smoker and non-smoker in terms of serum TAC values but at day 15, serum TAC values were significantly higher in the exposure group. Also, TAC of salivawas significantly higher in the passive smoker group at baseline and at day 15 but at day 30, the difference in this respect between the two groups was not statistically significant. Conclusion: Based on the obtained results, changes in TAC of serum and saliva in rats due to exposure to cigarette smoke were compensated by their immune system activity. However, further investigations are still required in this respect.